2020
DOI: 10.48550/arxiv.2007.09435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multilevel Motion Planning: A Fiber Bundle Formulation

Andreas Orthey,
Sohaib Akbar,
Marc Toussaint

Abstract: Motion planning problems involving high-dimensional state spaces can often be solved significantly faster by using multilevel abstractions. While there are various ways to formally capture multilevel abstractions, we formulate them in terms of fiber bundles, which allows us to concisely describe and derive novel algorithms in terms of bundle restrictions and bundle sections. Fiber bundles essentially describe lower-dimensional projections of the state space using local product spaces. Given such a structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(41 citation statements)
references
References 124 publications
0
41
0
Order By: Relevance
“…Second, prioritization frameworks [3,10,58] can be used, where robots are ranked and planned in sequential order, while imposing the previously planned movements as constraints for the next robot. Solutions to single robots act as admissible heuristics [37], but backtracking in continuous spaces can often be time consuming. Several approaches exist to avoid backtracking, for example by analyzing start or goal conflicts [54] or biasing towards local minimum solutions [35].…”
Section: A Multi-robot Motion Planningmentioning
confidence: 99%
“…Second, prioritization frameworks [3,10,58] can be used, where robots are ranked and planned in sequential order, while imposing the previously planned movements as constraints for the next robot. Solutions to single robots act as admissible heuristics [37], but backtracking in continuous spaces can often be time consuming. Several approaches exist to avoid backtracking, for example by analyzing start or goal conflicts [54] or biasing towards local minimum solutions [35].…”
Section: A Multi-robot Motion Planningmentioning
confidence: 99%
“…Finally, MOTIONBENCHMAKER has already been used to create a diverse set of datasets suitable for learning-based methods [8], [43], for hyper-parameter tuning methods [44], for planning under uncertainty [45], for planning in partially observable environments [46] and for planning on different abstraction levels [5], [47].…”
Section: Example Usecasesmentioning
confidence: 99%
“…In previous work, we and other research teams have shown that we can often efficiently solve high-dimensional planning problems by using admissible lower-dimensional projections of the state space, a topic we refer to as multilevel motion planning [22,5,67,75,97]. When using a multilevel motion planning framework, we can often use solutions to simplified planning stages as admissible heuristics for the original problem [70,1].…”
Section: Introductionmentioning
confidence: 99%
“…When using a multilevel motion planning framework, we can often use solutions to simplified planning stages as admissible heuristics for the original problem [70,1]. To efficiently exploit those admissible heuristics, we can use biased sampling methods [67,74], which we can combine with classical planning algorithms like the rapidly-exploring random tree algorithm [63], the probabilistic roadmap planner [65], its optimal star versions [67] or the fast marching trees planner [74]. However, while showing promising runtimes, those algorithms are prone to get trapped when run on problems involving narrow passages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation